Land, water, and development : sustainable management of river basin systems - Newson, Malcolm David (London ; New York : Routledge, 1997)
This is a fully revised and expanded second edition of Malcolm Newson's acclaimed book. Exploring in greater depth the meaning of sustainability in river basin development this new edition:* highlights the rapid evolution of practical concepts since the Rio Earth Summit* features new illustrations and case studies from Australia, South Africa and Israel* makes the ecosystem model more explicit throughout* strengthens coverage of the linkages between land and water management.
1. History of river basin management -- 2. Natural river basins : transfer systems -- 3. Land and water : interactions -- 4. Managing land and water in the developed world : an international survey -- 5. River basins and development -- 6. Technical issues in river basin management -- 7. Institutional issues in river basin management -- 8. Sustainable river basin management : issues of the knowledge base -- 9. Land and water : towards systems of management in a period of change.
Includes bibliographical references (pages 374-407)-and indexes.
Print version record.
English.
1640038
eBooks on EBSCOhost
Keywords: Watershed management; Water resources development; Sustainable development; Bassins hydrographiques -- Gestion; Ressources en eau -- Exploitation; Développement durable; water resources development; sustainable development; BUSINESS & ECONOMICS -- Real Estate -- General; Sustainable development; Water resources development; Watershed management; Rivierbekkens; Waterhuishouding; Duurzame ontwikkeling; Recursos naturais (utilizacao)